On the Experimental Investigation of the Angular Distributions in the Reaction 112Cd(p,γ)113In - Zyriliou, A.; Khaliel, A.; Mertzimekis, T. J. (HNPS Advances in Nuclear Physics, 2019)
Some of the mid–weight nuclei lie in the region of the isotopic chart where the astrophysical p-process has a prominent role in the nucleosynthetic scenarios. Experimentally deduced reaction cross section data can provide stringent tests for the astrophysical models, especially at low energies. In this framework, the reaction 112Cd(p,γ)113In has been studied experimentally at four proton beam energies 2.8 ≤ Ep≤ 3.4 MeV, partly inside the astrophysically interesting Gamow window. Proton beams were provided by the 5.5 MV T11 Van de Graaff Tandem Accelerator of the Institute of Nuclear Physics of the National Center for Scientific Research (NCSR) “Demokritos”. In–beam spectroscopy was carried out with an array of four HPGe detectors sitting on a rotating table. In total, eight (8) different angles were used to record gamma–ray spectra. Special focus was given on constructing the angular distribution of each gamma–ray feeding the ground state of 113In directly, so as to determine the reaction cross sections from the in–beam data, exclusively. The resulting cross sections were compared to Hauser–Feshbach calculations using the code TALYS v1.9.